Pengaruh Gaya Kepemimpinan, Reward, Dan Punishment Terhadap Kinerja Pegawai Dinas Sosial Kota Batu - Ahmad Zied Almathori Zohri; Abdul Kodir Djaelani; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the influence of leadership styles, rewards, and punishments on the performance of Social Service employees in Batu City 2023. The type of research used is quantitative research. The sample used in this study was 50 employee respondents. Data collection was carried out by distributing questionnaires (questionnaire). Data analysis used in this study used validity test, reliability test, normality test, multicollinearity, heteroscedasticity, simultaneous F test, coefficient of determination, and t test. The results of this study simultaneously the variables of leadership style, reward, and punishment have an effect on the performance of Social Service employees in Batu City 2023. While partially 1) the leadership style variable has a significant and positive effect on employee performance, 2) the reward variable has a significant and positive effect on performance employees, and 3) the punishment variable has a significant and positive effect on employee performance. Keywords: leadership style, reward, punishment, employee performance